Analysis of IG FINFET based N-Bit Barrel Shifter - Kandasamy, Nehru; Telagam, Nagarjuna; Kumar, Praneeth; Gopal, Venu (International Journal of Integrated Engineering, 2020)
This paper presents a new energy efficient N-bit barrel shifter using IG FinFET in 20 nm technology. The independent gate based FinFET device having more attractive features than standard CMOS technology. The proposed N-bit barrel shifter using independent gate FINFET device reduces the low power consumption over MOSFET and simulation results are performed using H spice software. In this work, it is presented the electrical analysis in terms of signal delay propagation and energy consumption of compacted barrel circuit for shifting operation.